Interactions between gut microbiota and non-alcoholic liver disease: The role of microbiota-derived metabolites - Ding, Yufang; Yanagi, Karin; Cheng, Clint; Alaniz, Robert C.; Lee, Kyongbum; Jayaraman, Arul (Pharmacological research, 2019)
[Display omitted] There is increasing evidence that the intestinal microbiota plays a mechanistic role in the etiology of non-alcoholic fatty liver disease (NAFLD). Animal and human studies have linked small molecule metabolites produced by commensal bacteria in the gut contribute to not only intestinal inflammation, but also to hepatic inflammation. These immunomodulatory metabolites are capable of engaging host cellular receptors, and may mediate the observed association between gut dysbiosis and NAFLD. This review focuses on the effects and potential mechanisms of three specific classes of metabolites that synthesized or modified by gut bacteria: short chain fatty acids, amino acid catabolites, and bile acids. In particular, we discuss their role as ligands for cell surface and nuclear receptors regulating metabolic and inflammatory pathways in the intestine and liver. Studies reveal that the metabolites can both agonize and antagonize their cognate receptors to reduce or exacerbate liver steatosis and inflammation, and that the effects are metabolite- and context-specific. Further studies are warranted to more comprehensively understand bacterial metabolite-mediated gut-liver in NAFLD. This understanding could help identify novel therapeutics and therapeutic targets to intervene in the disease through the gut microbiota.